Sistem Informasi Manajemen KUKERTA Berbasis Web Pada UIN Jambi - Saputra, M. A. Ade; Siahaan, Kondar (LPPM Universitas Dinamika Bangsa, 2021)
In the process of implementing KUKERTA at LP2M UIN Sulthan Thaha Saifuddin Jambi, which has been carried out still uses manual methods ranging from registration, verification of required documents, location determination and reporting of activities, so it takes quite a long time to process the data collection and document validation and often causes error. The purpose of this research was to analyze the KUKERTA information system and design a web-based Kukerta information system at LP2M UIN Sulthan Thaha Saifuddin Jambi. In designing the Kukerta information system using UML (Unified Modeling Language) modeling, namely usecase diagrams, activity diagrams and class diagrams, and the making KuKerta information system interfaces using Balsamiq Mocups. This research produced a website-based KuKerta information system prototype at LP2M UIN STS Jambi which is expected to solve the problems both in terms of data processing, documenting reports and facilitating the implementation process of all interested parties.